D’Mask / Imran Danial Ahmad Latif ... [et al.] - Ahmad Latif, Imran Danial; Yusof, Nor Shuhadah; Ahmadani, Nur Adlina; Zamri, Nur Farhanah; Norhisham, Nurhidayu Afiqah (2021)
This report is written to understand the use of business model canvas (BMC) as well as the benefits of starting a business in a structural and organized method. Alexander Osterwalder is the creator of this model and it is a fantastic tool for understanding a company model in an organized, clear manner. Using this canvas, we will learn more about our consumers, what value propositions are given through which channels, and how a business generates money. We utilize the business model canvas to better understand our own or a competitor's company model. Our company, D’Mask, is a sole proprietorship business based in Danau Kota, Kuala Lumpur, which provides a contemporary cloth face masks that are both comfortable and protective as our response to curb the virus with the main objective of keeping the people saved. We do not set a specific customer segment as it is the responsibility of each people to wear a mask regardless of demographic factors. D’Mask is guaranteed to have a strong team to build up the business with an experienced and talented Marketing Manager, Financial Manager, Operations Manager, and finally Human Resource Manager. In the report, we have analyzed our two main competitors by using SWOT analysis and identify what are our strength, weaknesses, opportunities, and threats compared to them. It is a simple yet useful tool to help us build on what our company do well, addressing the lack in several areas, minimizing risks, as well as grabbing the best opportunity whenever possible. This report also contains the nine elements of business model canvas namely customer segments, value proposition, channels, customer relationship, revenue streams, key activities, key resources, key partnerships, and finally cost structure.